Pengujian Kualitas Air di Perairan Pantai Negeri Morella sebagai Habitat Kima (Tridacna sp.) - Ferliana Widyasari; Santoso Budi Widiarto; Gulam Arafat; Didik Setiadi; M. Nasrul Latulanit,; Arif Reza Fahlevi (Jurnal Airaha, 2016)
The aims of this study is to determine the water quality of Negeri Morella as one of Kima's habitat in Indonesia. Data analysis was done in laboratory and then paired with map according to coordinate sampling with Geographical Projection System using Datum WGS 1984. Based on the result of water quality test obtained, temperature value ranged from 26,9 to 27,4 0C, pH value ranged between 7,88 - 8.12, salinity values ranged from 33.06 to 33.54 ppt. The value of uniformity index (E) of phytoplankton obtained in Morella waters 0.6. The values obtained showed a moderate to high level of uniformity. Value Index dominance (D) phytoplankton obtained 0.233. This value indicates that the structure of the community found there are species that extreme dominate other species (close to 0). The abundance of zooplankton obtained 2,255 individuals / L. The type of zooplankton found in Negeri Morella is Candacia, Acartia sp, Euchaeta sp, Euchalanus sp, Corycaeus sp, macrosetella sp, Euterpina sp, Euchonchecia sp, Tortanus sp, Acrocalanus sp, Oitohona sp, Sagita sp, Ouklopleura, Larva Peneidae, Cirripedia, Echinodermata, Gastropoda dan Bivalvia.